2016
DOI: 10.1080/19942060.2016.1201544
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of bus aerodynamics on several classes of bridge decks

Abstract: This paper is focused on improving traffic safety on bridges under crosswind conditions, as adverse wind conditions can increase the risk of traffic accidents. Two ways to improve traffic safety are investigated: improving vehicle stability by means of wind fences installed on the bridge deck and by modifying the design parameters of the infrastructure. Specifically, this study examines the influence of different parameters related to the bridge deck configuration on the aerodynamic coefficients acting on a bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…The results also showed that the sudden changing of the aerodynamic forces caused by the tower may be shorter than the average driver reaction time and thus the influence of crosswinds on lightweight vehicles such as buses and trucks can induce traffic accidents, even when exposed to relatively low wind velocities. Alonso-Estébanez et al (2017) studied the performance of an articulating wind shield by investigating the effect of the angle between the wind shield and the horizontal plane on vehicle aerodynamics. Results indicated that the articulating wind shield was better at protecting vehicles from crosswinds than crash barriers alone.…”
Section: Introductionmentioning
confidence: 99%
“…The results also showed that the sudden changing of the aerodynamic forces caused by the tower may be shorter than the average driver reaction time and thus the influence of crosswinds on lightweight vehicles such as buses and trucks can induce traffic accidents, even when exposed to relatively low wind velocities. Alonso-Estébanez et al (2017) studied the performance of an articulating wind shield by investigating the effect of the angle between the wind shield and the horizontal plane on vehicle aerodynamics. Results indicated that the articulating wind shield was better at protecting vehicles from crosswinds than crash barriers alone.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many pieces of research to estimate the aerodynamic behaviors of the train under a crosswind environment using the full-scale experiments, scaled wind tunnel tests and CFD simulations CONTACT Nan Zhang nzhang@bjtu.edu.cn (Alonso-Estébanez, Del Coz Díaz, Álvarez Rabanal, & Pascual-Muñoz, 2017;Baker, Jones, Lopez-Calleja, & Munday, 2004;Gallagher et al, 2018;Niu, Zhou, & Liang, 2018;Suzuki, Tanemoto, & Maeda, 2003). In these investigations, usually the train runs on the flat ground or embankment, and the movement of the train is created by means of the resultant velocity V r imposed on a static vehicle, as seen in Figure 1, depending on the train speed V t and incoming wind speed V w with a wind angle of α.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, for the train-bridge system with a moving vehicle, it is not easy to measure the aerodynamic forces on the bridge. At the same time, with the rapid development of computer technology, the CFD approach is also widely approved and adopted in the studies (Alonso-Estébanez et al, 2017;Mosavi, Shamshirband, Salwana, Chau, & Tah, 2019;Niu et al, 2018;Sun, Song, & An, 2012;Yao, Guo, Sun, & Yang, 2015;Zhang, Yu, Zhang, Wu, & Li, 2019), which can better capture the flow characteristics around train-bridge system and easily obtain the aerodynamics affiliated to the train and bridge, compared with a moving vehicle wind tunnel test and full-scale experiment. At present, the dynamic mesh and sliding mesh method are usually used to present the movement of the train in the simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Since the TMD concept was first investigated by Frahm [6], much research has been carried out to examine its effectiveness for various dynamic load applications. Much of the previous research efforts were focused on optimizing the TMD parameters and suppressing the bridge vibration under wind or seismic loads [7,8,9,10,11,12,13,14,15]. However, we found few studies on applying TMDs to suppress bridge vibrations induced by combined wind and traffic loads [16,17].…”
Section: Introductionmentioning
confidence: 99%